2001
DOI: 10.1137/s1064827500369967
|View full text |Cite
|
Sign up to set email alerts
|

A New Fast-Multipole Accelerated Poisson Solver in Two Dimensions

Abstract: Abstract. We present an adaptive fast multipole method for solving the Poisson equation in two dimensions. The algorithm is direct, assumes that the source distribution is discretized using an adaptive quad-tree, and allows for Dirichlet, Neumann, periodic, and free-space conditions to be imposed on the boundary of a square. The amount of work per grid point is comparable to that of classical fast solvers, even for highly nonuniform grids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
152
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(153 citation statements)
references
References 31 publications
0
152
0
1
Order By: Relevance
“…We refrain from giving more details since our code is not entirely optimal with respect to the latest development in the field. More efficient and consequent implementations for some kernels in 2D do exist [32,15]. We speculate that speedups with a factor of 5 -10 are possible for the problem sizes treated in this paper.…”
Section: Iterative Solution and Fast Multipolesmentioning
confidence: 87%
See 3 more Smart Citations
“…We refrain from giving more details since our code is not entirely optimal with respect to the latest development in the field. More efficient and consequent implementations for some kernels in 2D do exist [32,15]. We speculate that speedups with a factor of 5 -10 are possible for the problem sizes treated in this paper.…”
Section: Iterative Solution and Fast Multipolesmentioning
confidence: 87%
“…A more radical way to go is to abandon the idea of solving integral equations completely, and instead compute the solution to the stress problem directly, as a sum of reflected layer potentials. Promising work on this type of fast direct solvers have been reported by Ethridge and Greengard for Laplace's and Poisson's equations on the unit square, and extensions to complex geometry are underway [15].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two such fast direct solver classes are fast Fourier transform (FFT) or cyclic reduction accelerated finite difference methods and fast multipole accelerated integral methods. While FFT accelerated finite difference solvers is the classic choice, Ethridge and Greengard [12] and Huang, Cheng, and Leiterman [23] recently showed that these can be outperformed by integral method solvers. The work per grid point for the solver classes is comparable, at least for moderate precision arithmetic.…”
Section: Introductionmentioning
confidence: 99%